If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 18Z + -7 = 9Z + 50 + -7Z Reorder the terms: 9 + -7 + 18Z = 9Z + 50 + -7Z Combine like terms: 9 + -7 = 2 2 + 18Z = 9Z + 50 + -7Z Reorder the terms: 2 + 18Z = 50 + 9Z + -7Z Combine like terms: 9Z + -7Z = 2Z 2 + 18Z = 50 + 2Z Solving 2 + 18Z = 50 + 2Z Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Add '-2Z' to each side of the equation. 2 + 18Z + -2Z = 50 + 2Z + -2Z Combine like terms: 18Z + -2Z = 16Z 2 + 16Z = 50 + 2Z + -2Z Combine like terms: 2Z + -2Z = 0 2 + 16Z = 50 + 0 2 + 16Z = 50 Add '-2' to each side of the equation. 2 + -2 + 16Z = 50 + -2 Combine like terms: 2 + -2 = 0 0 + 16Z = 50 + -2 16Z = 50 + -2 Combine like terms: 50 + -2 = 48 16Z = 48 Divide each side by '16'. Z = 3 Simplifying Z = 3
| 2y^2-26y=0 | | -6(x+3)+4x+5=6x+12 | | 4-x^2-2x=35 | | 60-2x=81+x | | 25x^2y^4+10xy^3-15x^2y^5=0 | | 6x^2+15x-7=0 | | f=1/2(hp) | | 7t-16=-51+2t | | 0.75x^2+1.5x-150=0 | | 3-2x^2-8=0 | | 0.3n=-12 | | 4+3x-0.5x^3=0 | | In(e^3)=In(e^3)+In(e^5) | | 8(2q-2)= | | 2(w^2-36)=0 | | 8x+4z=5+7y | | f(x)=3x^2+6x-4 | | 3e^2x=44 | | ln(x^5/x^4) | | 3x^2-5x+x^2-5x=x | | m=2/3.(7.-9) | | 3x^4-2x^3+22x^2-18x-45=0 | | -8=4+0.125b | | 2b^2+17b+35=0 | | 5(8y-9)-(7y+6)= | | 5y/y^2-2y | | 2cos(6x)+1=0 | | 4p-24=-4+8p | | 5y/y*2-2y | | 3m-20=-34+m | | 317g=kg | | 103x-4=-215x+632 |